2018
DOI: 10.1097/brs.0000000000002676
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Daily Living After Long Level Fusion in Adult Spinal Deformity

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Before surgery, patients should be made aware of the fact that higher ASA scores are associated with both perioperative complications and increased SRFD. Similar to the findings of past studies, 7,[9][10][11][12]17 fusion length was significantly correlated with SRFD for sanitation activity, lower body activities, and total sum. However, sitting on the floor was not affected by fusion length.…”
Section: Key Results and Interpretationsupporting
confidence: 88%
See 4 more Smart Citations
“…Before surgery, patients should be made aware of the fact that higher ASA scores are associated with both perioperative complications and increased SRFD. Similar to the findings of past studies, 7,[9][10][11][12]17 fusion length was significantly correlated with SRFD for sanitation activity, lower body activities, and total sum. However, sitting on the floor was not affected by fusion length.…”
Section: Key Results and Interpretationsupporting
confidence: 88%
“…However, contrary to our expectations, the sagittal parameters including LL, sacral slope, PT, thoracic kyphosis, and SVA did not show a significant correlation with SRFD, except for PI-LL, which only correlated with 1 category (lower body activities). Furthermore, the study by Kim et al 10 showed that PI-LL, PT, and SVA did not affect daily living activities after long segmental fusion. The results of our study were on similar grounds to that study.…”
Section: Key Results and Interpretationmentioning
confidence: 94%
See 3 more Smart Citations